SunTzu on Battlegrounds and Strategies: Seven Propositions for Successful Market Targeting and Penetration Strategies for SMEs - Soo Jiuan Tan; Khai Sheang Lee; Guan H Lim (Asian Academy of Management Journal, 1998)
SunTzu on Battlegrounds and Strategies: Seven Propositions for Successful Market Targeting and Penetration Strategies for SMEs (PDF not available)